An Analysis of Racial Diversity in the Breast Reconstruction and Aesthetic Surgery Literature - Sahil Chawla, HBsc; Hanaa Shihadeh, MD; Ashit Patel, MBChB (Plastic and Reconstructive Surgery, Global Open, 2022)
Background:. Racial disparities in the visual representation of patients in the plastic surgery literature can contribute to health inequities. This study evaluates racial diversity in photographs published in the aesthetic and breast reconstruction literature. Methods:. A photogrammetric analysis of plastic surgery journals from the USA, Canada, and Europe was performed. Color photographs depicting human skin, pertaining to breast reconstruction and aesthetic surgery in 2000, 2010, and 2020, were categorized as White (1–3) or non-White (4–6) based on the Fitzpatrick scale. Results:. All journals demonstrated significantly more White skin images than non-White for all procedures (P < 0.05) except blepharoplasty and rhinoplasty. Blepharoplasty was the only procedure with more non-White images (P = 0.02). When examining USA journals, significant differences were not found in blepharoplasty, rhinoplasty, and male chest surgery. European journals published a greater proportion of non-White images than USA journals (P < 0.0001). There was a decreasing rate of change in diversity with 15.5% of images being non-White in 2000, 32.7% in 2010, and 40.7% in 2020 (P < 0.01). Percentage of non-White images varied by geographical region and ranged from 3.6% in Oceania to 93.5% in Asia (P < 0.01). Conclusions:. Diversity of patient populations depicted in plastic surgery literature has increased over the past two decades. Despite this improvement, the racial diversity seen in photographs published in the literature does not adequately reflect this demographic for aesthetic and breast procedures. Equitable visual representation may promote cultural competency and improve care for the populations we serve.